Cybercrime dan Media Sosial: Analisis Hukum terhadap Tren Peningkatan Tindak Pidana di Era Digital - Alejandro Morion Ruben Thomas; Happy Yulia Anggraeni (Jurnal Hukum Lex Generalis, 2025)
The rapid evolution of digital technology has brought significant benefits to society, yet it has also triggered the emergence of increasingly complex forms of cybercrime. Incidents such as data theft, online fraud, and system intrusion occur in unpredictable patterns, as technological innovation progresses faster than regulatory frameworks can adapt. This study examines the dynamics of cybercrime through four main dimensions: regulatory vulnerabilities, the level of digital literacy among the public, the effectiveness of law enforcement, and the social as well as psychological implications experienced by victims. Using a literature-based approach, this analysis reviews studies published within the last five years to understand how policy, technology, and human behavior interact within the realm of digital security. The findings reveal that low public awareness of data protection, limited technical capacity among law enforcement agencies, and the severe psychological impacts on victims remain critical challenges. This study highlights the need for a multidisciplinary response integrating legal, technical, and social interventions to ensure a safer and more sustainable digital ecosystem.